(untitled) (Research, Society and Development, 2021)
The objective of this review was to evaluate the effects of nutritional patterns indicated for the management of Polycystic Ovary Syndrome (PCOS). For this purpose, a bibliographic search was carried out in the PubMed database, comprising articles published between 2018 and 2021, in English and Portuguese. A total of 1141 articles were found, and 610 articles were excluded for being unrelated to the topic studied or for not being freely available. Of the 531 articles, 41 were selected and 20 studies were included in the review. As a result, the studies suggest that nutritional interventions, such as low-carbohydrate (<45%) and low-glycemic index diets, supplementation of omega-3 and phenolic compounds, higher ingestion of legumes and vegetables, appear to have a beneficial effect, when adjusted to individual need, on clinical and biochemical manifestations in women with PCOS. The present study is in line with the evidence that a variety of balanced dietary approaches can and should be recommended for the management of these manifestations. However, the general principles of healthy eating, as recommended for the general population, are applicable to all women with PCOS. For these, it is not known so far whether or not there is limited evidence that any specific type of diet is better than another.